CCR5 Gene Editing of Resting CD4+ T Cells by Transient ZFN Expression From HIV Envelope Pseudotyped Nonintegrating Lentivirus Confers HIV-1 Resistance in Humanized Mice - Guohua Yi; Jang Gi Choi; Preeti Bharaj; Sojan Abraham; Ying Dang; Tal Kafri; Ogechika Alozie; Manjunath N Manjunath; Premlata Shankar (Elsevier, 2014)
CCR5 disruption by zinc finger nucleases (ZFNs) is a promising method for HIV-1 gene therapy. However, successful clinical translation of this strategy necessitates the development of a safe and effective method for delivery into relevant cells. We used non-integrating lentivirus (NILV) for transient expression of ZFNs and pseudotyped the virus with HIV-envelope for targeted delivery to CD4+ T cells. Both activated and resting primary CD4+ T cells transduced with CCR5-ZFNs NILV showed resistance to HIV-1 infection in vitro. Furthermore, NILV transduced resting CD4+ T cells from HIV-1 seronegative individuals were resistant to HIV-1 challenge when reconstituted into NOD-scid IL2rγc null (NSG) mice. Likewise, endogenous virus replication was suppressed in NSG mice reconstituted with CCR5-ZFN-transduced resting CD4+ T cells from treatment naïve as well as ART-treated HIV-1 seropositive patients. Taken together, NILV pseudotyped with HIV envelope provides a simple and clinically viable strategy for HIV-1 gene therapy.